2011
DOI: 10.1007/s11904-011-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use: Impact on Adherence and HIV Medical Treatment

Abstract: Substance use is highly prevalent among people living with HIV/AIDS, is often comorbid with other mental health problems, related to poor HIV medical outcomes, and, is associated with poor medication and treatment adherence. The current review reports on the recent state of the literature in terms of substance use and its relation to HIV medication and treatment adherence, and offers recommendations for advancing treatment and secondary HIV prevention efforts. Identifying substance users within HIV primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1
9

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 114 publications
5
105
1
9
Order By: Relevance
“…Substance use is also associated with nonadherence. 41 In the same way, alcohol consumption demonstrates a relationship to poor adherence. 42 On the other hand, our study showed a significant relationship between adherence and being ART naïve.…”
Section: ■■ Discussionmentioning
confidence: 96%
“…Substance use is also associated with nonadherence. 41 In the same way, alcohol consumption demonstrates a relationship to poor adherence. 42 On the other hand, our study showed a significant relationship between adherence and being ART naïve.…”
Section: ■■ Discussionmentioning
confidence: 96%
“…For example, lifestyles of substance abuse may have negative effects on adherence to medication. [3][4][5][6] Likewise, the factors affecting adherence may differ in specific subgroups, such as pregnant women for whom concerns for fetal safety may be a reason for not taking medication as prescribed. 7 Irrespective of the underlying factors for poor adherence, it has nefarious consequences on clinical outcomes, reduces quality of life, and wastes medication.…”
Section: Introductionmentioning
confidence: 99%
“…In considering the role of these medications, it will be crucial for investigators to take into account adherence because being prescribed an antiretroviral medication does not necessarily mean an individual is taking is regularly. Research is limited and findings are mixed as to whether marijuana use lowers adherence or increases it potentially by reducing unpleasant side effects [91], and it may be that dependent individuals are negatively impacted whereas casual users are not [92].…”
Section: Critique Of the Current Literature And Future Research Priormentioning
confidence: 99%